A study of the middle atmospheric thermal structure over western India: Satellite data and comparisons with models. Issue 11 (1st December 2017) - Sharma, Som; Kumar, Prashant; Vaishnav, Rajesh; Jethva, Chintan; Beig, G.
Abstract: Long term variations of the middle atmospheric thermal structure in the upper stratosphere and lower mesosphere (20–90 km) have been studied over Ahmedabad (23.1°N, 72.3°E, 55 m amsl), India using SABER (Sounding of the Atmosphere using Broadband Emission Radiometry) onboard TIMED (Thermosphere, Ionosphere, Mesosphere, Energetics and Dynamics) observations during year 2002 to year 2014. For the same period, three different atmospheric models show over-estimation of temperature (∼10 K) near the stratopause and in the upper mesosphere, and a signature of under-estimation is seen above mesopause when compared against SABER measured temperature profiles. Estimation of monthly temperature anomalies reveals a semiannual and ter-annual oscillation moving downward from the mesosphere to the stratosphere during January to December. Moreover, Lomb Scargle periodogram (LSP) and Wavelet transform techniques are employed to characterize the semi-annual, annual and quasi-biennial oscillations to diagnose the wave dynamics in the stratosphere-mesosphere system. Results suggested that semi-annual, annual and quasi-biennial oscillations are exist in stratosphere, whereas, semi-annual and annual oscillations are observed in mesosphere. In lower mesosphere, LSP analyses revealed conspicuous absence of annual oscillations in altitude range of ∼55–65 km, and semi-annual oscillations are not existing in 35–45 km. Four monthly oscillations are also reported in the altitude range of about 45–65 km. The temporal localization of oscillations using wavelet analysis shows strong annual oscillation during year 2004–2006 and 2009–2011.